Robot-assisted modifications of gait in healthy individuals - Kim, Seok Hun; Banala, Sai K; Brackbill, Elizabeth A; Agrawal, Sunil K; Krishnamoorthy, Vijaya; Scholz, John P (Experimental brain research, 2010)
This study investigated whether short-term modifications of gait could be induced in healthy adults and whether a combination of kinetic (a compliant force resisting deviation of the foot from the prescribed footpath) and visual guidance was superior to either kinetic guidance or visual guidance alone in producing this modification. Thirty-nine healthy adults, 20-33 years old, were randomly assigned to the three groups receiving six 10-min blocks of treadmill training requiring them to modify their footpath to match a scaled-down path. Changes of the footpath, specific joint events and joint moments were analyzed. Persons receiving combined kinetic and visual guidance showed larger modifications of their gait patterns that were maintained longer, persisting up to 2 h after intervening over-ground activities, than did persons receiving training with primarily kinetic guidance or with visual guidance alone. The results emphasize the short-term plasticity of locomotor circuits and provide a possible basis for persons learning to achieve more functional gait patterns following a stroke or other neurological disorders.